ASSESSMENT OF REPRODUCTIVE DISORDER REMEDIAL PRACTICE (RDRPA) ADOPTION BY DAIRY FARMERS IN UNDULATING PLAIN REGION OF PUNJAB - KASRIJA, R; VERMA, H K; GANDOTRA, V K (The Indian Journal of Animal Reproduction, 2016)
A study was conducted in the undulating plain region of Punjab to assess the reproductive disorder remedial practice adoption (RDRPA) level of dairy farmers possessing small (1-9 animal), medium (10-30 animal) and large (>30 animal) dairy units. There was significant difference (p<0.05) in RDRPA score of small and large dairy farmers. Majority of the dairy farmers had medium RDRPA level, which positively correlated with education, land holding, training, mass media exposure, social participation and extension contacts of farmers. The lack of awareness followed by cost factor were main factor for non-adoption of RDRPA. In brief, there is urgent need for spreading awareness by extension specialists and formulating suitable strategy for enhancing adoption level for curtailing reproductive disorders